Student Training and Workforce Development at the USGS Water Resources Research Institutes. (19th September 2018) - Donohue, Mary J.; Lerner, Darren T.
Abstract: Measures of student training and workforce development are key academic, social, and economic metrics. A principal component of the United States Geological Survey Water Resources Research Act Program is the training of water scientists and engineers through participation in research and other mentoring. This training occurs through Water Resources Research Institutes known as the National Institutes for Water Resources. Though the institutes have a demonstrated record in student training, there has been limited synthesis of data on students trained at state and national levels to clarify these contributions to workforce development. We investigated student support at the 54 institutes from 2000 through 2015 using archived data, including a survey of institute practices. Institutes play a key role in water resources training within a greater science, technology, engineering, and mathematics (STEM) framework. Institutes pooled supported on average 678 ( sd = 83) students per year (range 518 to 788), providing 10, 853 student support years during this period. Individual institutes supported on average 201 ( sd = 102) students per year (range 76 to 646). While 98% of institutes used data on students supported to fulfill required reporting, fewer used these data for institute promotion (45%), website or social media engagement (41%), and development/donor activities (16%). Consistency in data collection and management among institutes, coupled with refined use of student support data, such as documenting disciplines and dates of degrees earned, post‐support job placement, and diversity and equity metrics, would further demonstrate the value of this investment in student training and workforce development.